Two Faces of Anti-crisis Management: from Definitions to Concepts = Dwa oblicza zarządzania antykryzysowego: od definicji do koncepcji - Czarnecki, Maciej; Starosta, Anna (Zielona Góra: Faculty of Economics and Management Press)
Issues related to crisis in business, although present in literature on management for a long time, still remain unexplained to a great extent. Studying the subject literature leads to the conclusion that the concept of anti-crisis management, although present in literature for many years, is understood in a number of different ways.
Keywords: kryzys; zarządzanie antykryzysowe; system wczesnego ostrzegania; odporność na kryzys; crisis; anti-crisis management; early warning system; resistance to crisis